2012
DOI: 10.1111/j.1365-2249.2011.04498.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Clostridium tyrobutyricum in acute dextran sodium sulphate-induced colitis: differential regulation of tumour necrosis factor-α and interleukin-18 in BALB/c and severe combined immunodeficiency mice

Abstract: SummaryOne of the promising approaches in the therapy of ulcerative colitis is administration of butyrate, an energy source for colonocytes, into the lumen of the colon. This study investigates the effect of butyrate producing bacterium Clostridium tyrobutyricum on dextran sodium sulphate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 52 publications
2
34
1
Order By: Relevance
“…In addition, several recent studies focusing on the role of orally given butyrate producing bacteria like Butyricicoccus spp. or Clostridium tyrobutyricum, have revealed that the bacteria increase the butyrate levels in the colon and subsequently cure UC (Hudcovic et al, 2012;Eeckhaut et al, 2013). All these facts and our own results in this study consistently indicate that orally given butyrate could be a potential route to treat UC.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, several recent studies focusing on the role of orally given butyrate producing bacteria like Butyricicoccus spp. or Clostridium tyrobutyricum, have revealed that the bacteria increase the butyrate levels in the colon and subsequently cure UC (Hudcovic et al, 2012;Eeckhaut et al, 2013). All these facts and our own results in this study consistently indicate that orally given butyrate could be a potential route to treat UC.…”
Section: Discussionsupporting
confidence: 74%
“…45,64 Furthermore, administration of Clostridium tyrobutyricum depressed expression of proinflammatory cytokines such as tumor necrosis factor-a and interleukin-18 in the descending colon of dextran sodium sulfate-treated mice. 59 Similar results have also been described in cytokine-mediated gastrointestinal diseases, 65 alcoholinduced inflammation, 66,67 and even chemotherapy-induced mucositis. 34 Besides, administration of probiotics (Jinshuangqi tablets) for 7 days significantly improved levels of IgA, IgG, IgM, interelukin-2, and CD4þ in the serum of colorectal cancer patients, demonstrating the capacity for probiotics to modulate adaptive immunity.…”
Section: Probiotics and Immunitysupporting
confidence: 68%
“…and Clostridium tyrobutyricum to adjust mucin secretion could therefore play a pivotal role in restoring microbiota composition and mucosal immunity in chemotherapy-treated patients. [58][59][60] Furthermore, certain probiotics have the potential to modulate cell kinetics by adjusting homeostasis between apoptosis and proliferation. For example, Lactobacillus rhamnosus regulated cellular proliferation and migration and mitogen-activated protein kinase pathways, responsible for cell proliferation, differentiation, and cytoprotection.…”
Section: Maintenance Of the Gut Barriermentioning
confidence: 99%
“…Hence, conventionalization with the whole gut microbiota and the introduction of a single bacterial strain in GF mice appear to have opposite consequences for small intestinal ANGPTL4 expression. Interestingly, C. tyrobutyricum was successfully used to alleviate DSS-induced colitis in mouse models (27). Butyrate-driven ANGPTL4 may therefore participate in the anti-inflammatory effects of SCFAs within the GI tract because SCFAs have been shown previously to protect mice from experimental colitis (49).…”
Section: Discussionmentioning
confidence: 99%
“…We set out to investigate the impact of a single butyrate-producing bacterial species on intestinal ANGPTL4 expression. Male C57Bl/6J GF mice were monocolonized from birth with C. tyrobutyricum (DSM 2637), Table 1 which is able to ferment a wide range of carbohydrates into butyric acid (27). ANGPTL4 expression in the ileum and in colonic epithelial cells was higher in the monoassociated mice compared with the GF mice (Fig.…”
Section: Butyrate Induces Angptl4 Expression In a Ppar-␥-independent mentioning
confidence: 99%